Antifungal Activity Test of Robusta Coffee (Coffea canephora) Bean Ethanol Extract Against Candida albicans, Malassezia furfur, and Aspergillus oryzae Using the Agar Diffusion Method - Fajri, Ainun Nurul (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
The ethanol extract of robusta coffee beans (Coffea canephora) contains bioactive compounds primarily chlorogenic acid that may exert antifungal effects. This study evaluated the antifungal activity of the extract against Candida albicans, Malassezia furfur, and Aspergillus oryzae using the agar diffusion method. A preliminary screening at 0.1% concentration demonstrated that the extract inhibited the growth of all test fungi. In subsequent assays, extract concentrations ranging from 0.5% to 32% were tested, revealing a dose-dependent increase in inhibition zone diameters. The maximum inhibition was observed at 32%, with zones measuring 19.04 mm for C. albicans, 17.65 mm for M. furfur, and 16.97 mm for A. oryzae. These results, in comparison with the positive control (ketoconazole), suggest that the robusta coffee bean extract has substantial potential as a natural antifungal agent